Post-MH370 Incident: A comparative study of social media users ’perception in China and Malaysia - Wang, Changsong; Ahmad, Jamilah (Registrar of Newspapers for India (RNI), 2018)
The flow of information experienced complexity uncertainty and ambiguity in terms of information adequacy when Malaysia Airlines flight MH370 went missing. This incident demonstrated an unprecedented international humanitarian response from the technology sector. This study discovered that most respondents from Mainland China and Malaysia access information about Malaysia Airlines flight MH370 during and after the tragic incident through social media. This study revealed significant difference of active social media users ’perceptions on this incident in these two countries. On one hand, social networking sites such as Facebook (in Malaysia), Weibo and Wechat (in China), become the public opinion field that illustrates sorts of openness and negotiation in Malaysia and China. This study, instead of conventional crisis communication approach, specifically examined active online users in both countries, as it aims to make a valuable contribution by synthesizing current research and identifying areas for investigation for each aspect of the survey process. Two hundred questionnaires had been collected from respondents in China and Malaysia respectively. The survey results contributed to mechanism of crisis communication for henceforth similar incident in the future. There is no doubt that the portrait of Malaysia Airlines on social media in these two countries affected its organizational reputation. However, the participants from Malaysia and China showed a very average level of confidence to empower themselves to enhance dialog capacity among various stakeholders for this incident.